Efeitos do exercício físico multimodal nas concentrações plasmáticas de biomarcadores, funções cognitivas e funcionalidade em pacientes com doença de Alzheimer - Santos, Marcelo Garuffi [UNESP] (2013)
The Alzheimer's disease (AD), progressive and neurodegenerative disease represents the major type of dementia currently observed, showing high prevalence. Several studies aims to investigate the relationship between biomarkers and AD, including genetic factors such as APOE-ε4 , and pro inflammatory cytokines, such as interleukins and tumor necrosis factor (TNF) and verify the effects of exercise for these patients. Thus, the present study aimed to investigate the effects of a multimodal exercise program on plasma concentrations of inflammatory biomarkers, cognitive functions and functionality in patients with AD. The study has a longitudinal character and the sample was divided into two groups: 1) Training Group, including 17 patients in the mild and moderate stages of the disease, undergoing a multimodal exercise program three times a week with 60 minutes duration for 4 months; 2) Social Gathering Group including 18 patients in the same stage of the disease, participants in a group of socializing with the same frequency and duration as the other group. Patients of both groups were evaluated using the battery of cognitive and motor testing, and the quantification of biomarkers of disease, such as IL-2, IL-6 and TNF- α. For the data normally distributed, we used two-way ANOVA. For the non-normal data was used Z-score, and then treated by the procedures described above. Correlations were treated by Spearman correlation. It was assumed significance level of 5% (p≤0.05) for all analyzes. Significant differences between groups for the Mini- Mental State Examination, Baecke Questionnaire, aerobic endurance test, and IL-6 were observed. It can be concluded that patients participating in the multimodal training improve physical activity levels, aerobic endurance, and IL-6 as well as patients who participate in group social interaction have benefits in global cognitive functions